Development of aluminum-phosphate hybrid materials via sol-gel route for additive manufacturing of photonic materials - Tayama, Gabriel Toshiaki [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Additive manufacturing (AM) is a technology with great potential for use in photonic applications because it overcomes the limitations of traditional manufacturing methods. Among the various AM techniques available, the vat-photopolymerization (VPP) is one of the few that meets the requirements for photonics manufacturing. However, one of the main challenges hindering the widespread adoption of VPP in optical device manufacturing is the limited availability of materials compatible with VPP techniques. The aim of this thesis was to develop, elucidate the structure of, fabricate via additive manufacturing, and study the optical properties of 3D printed parts of aluminum-phosphate hybrid materials. These materials were developed using the sol-gel route as candidates for the fabrication of active and passive photonic devices. These materials were additive manufactured via VPP using a custom-made AM system operating under intermittent exposure conditions. We developed a mathematical model describing the exposure profile output by this custom-made VPP setup, since its operating principle greatly differs from commercial platforms. Then, these new materials were 3D printed after characterizing their VPP parameters and photopolymerization kinetics. Lastly, we examined the optical homogeneity and anisotropy of additive manufactured elements from these materials. These goals were explored throughout five scientific publications, composing the five chapters of this thesis. In our first contribution, we synthesized photopolymerizable aluminum-phosphate sols, that were polymerized to result in organic-inorganic hybrid (OIH) materials composed by poly (2-hydroxyethyl methacrylate) chains with aluminum-phosphate groups covalently bonded to the polymeric backbone. These inorganic units provide numerous crosslinkers, resulting in a highly interconnected and interlocked inorganic/organic structure. The OIH materials were optically transparent between the 420 nm - 1100 nm, however, these materials showed low transmittance in the near-infrared region (NIR) due to the high organic content of these matrices. In a second contribution, we modified the synthesis route to achieve aluminum-phosphate-silicate OIH materials with higher inorganic mass concentration and improved transmittance in the NIR. We investigated in-depth the structure of these materials by means of solid-state NMR and observed that the inorganic network is formed by aluminum-phosphate units interconnected by silicate chains. The chemical environment of the phosphate and aluminate sites could be tuned based on the aluminum to phosphorus ratio, allowing the structure to be tailored in order to enhance the lanthanide ions hosting ability of these materials. These structural features present these materials as potential candidates to immobilize lanthanide ions for developing active optical components. In a third contribution, we developed and tested a mathematical model describing the exposure profile outputted by the custom-built printer employed in this work, allowing us to model the laser-resin interaction in this equipment, and to correlate the printing parameters measured for our materials with those of commercial AM setups. Furthermore, we identified that this printing system can, theoretically, print faster compared to commercial platforms under specific conditions of beam diameter and overlap between pulses. In a fourth contribution, we explored the additive manufacturing of the aluminum-phosphate-silicate resins. The evolution of the 3D printing parameters of these materials (critical energy and penetration depth), and of the photopolymerization kinetics with light intensity and silicate concentration was studied. These results indicate the shift of critical conversion towards higher polymerization degree as the concentration of silicate increases, which was associated to a higher tendency towards cyclization. These results were employed to validate a photochemical model published in the literature describing the laser-resin interaction in VPP systems, elucidating the link between critical energy and photopolymerization kinetics. In our last contribution, we studied the refractive index distribution and the presence of optical anisotropies in 3D printed lines. We identified that the 3D printed parts are optically homogenous, despite the presence of a gradient of polymerization degree associated to the penetration of the laser into the resin and the beam profile. Optical anisotropies were identified, and polarized micro-Raman measurements indicate that the birefringence arises from the shear stress perpendicular to the scan direction due to the inflow of monomer towards the polymerization spot.

A manufatura aditiva (MA) é uma tecnologia com grande potencial para aplicações em fotônica, pois contorna as limitações impostas por métodos tradicionais de manufatura. Entre as várias técnicas de MA disponíveis, a fotopolimerização em cuba (VPP) é uma das poucas que atende os requisitos de tolerância presente na fabricação de dispositivos fotônicos. No entanto, um dos principais desafios que impedem ampla adoção da VPP na fabricação de dispositivos ópticos é a baixa disponibilidade de materiais processáveis com as técnicas de VPP. O objetivo desta tese foi desenvolver, elucidar a estrutura, fabricar via manufatura aditiva e estudar as propriedades ópticas de peças impressas 3D de materiais híbridos de alumínio-fosfato. Esses materiais foram desenvolvidos utilizando a rota sol-gel como candidatos para a fabricação de dispositivos fotônicos ativos e passivos via impressão 3D. Esses materiais foram processados via VPP usando um sistema MA customizado, operando sob condições de exposição intermitente. Foi desenvolvido e testado um modelo matemático descrevendo o perfil de exposição produzido por esse sistema VPP customizado, uma vez que seu princípio operacional difere daquele de plataformas comerciais. Em seguida, os parâmetros de impressão 3D e a cinética de fotopolimerização desses novos materiais foram estudados, permitindo sua impressão 3D. Por fim, foi estudado a homogeneidade óptica e a presença de anisotropias ópticas em partes produzidas por MA desses materiais. Esses objetivos foram explorados ao longo de cinco publicações científicas, compondo os cinco capítulos desta tese. Em nossa primeira contribuição, sintetizamos soluções fotopolimerizáveis de alumínio-fosfato, resultando em materiais híbridos orgânico-inorgânicos (HOI) compostos por cadeias de poli (2- hidroxietil metacrilato) com grupos alumínio-fosfato covalentemente ligados ao esqueleto polimérico. Essas unidades inorgânicas atuam como ligações cruzadas, resultando em uma estrutura inorgânica- orgânica altamente interconectada e interligada. Os materiais obtidos são totalmente transparentes entre 420 nm - 1100 nm, porem possuem baixa transmitância na região do infravermelho próximo (NIR) devido ao alto teor orgânico dessas matrizes. Em uma segunda contribuição, modificamos a rota de síntese para obter materiais HOI de alumínio-fosfato-silicato com maior teor de massa inorgânica e melhor transmitância no NIR. Investigamos em detalhe a estrutura desses materiais por meio de RMN de estado sólido e observamos que a rede inorgânica é formada por unidades de alumínio-fosfato interligadas por cadeias de silicato. O ambiente químico dos sítios de fosfatos e alumínio podem ser modificados por meio da razão alumínio para fosforo, permitindo que a estrutura seja otimizada para a introdução de íons lantanídeos. Essas características estruturais apresentam esses materiais como potenciais candidatos à imobilização de íons lantanídeos para o desenvolvimento de componentes ópticos ativos. Em uma terceira contribuição, desenvolvemos e testamos um modelo matemático descrevendo o perfil de exposição produzido pela impressora personalizada empregada neste trabalho, permitindo-nos modelar a interação laser-resina e correlacionar os parâmetros de impressão medidos para nossos materiais com aqueles de plataformas comerciais de MA. Além disso, identificamos que este sistema de impressão pode, teoricamente, imprimir mais rápido comparado a plataformas comerciais, desde que condições específicas de diâmetro do feixe e sobreposição entre pulsos sejam atendidas. Em uma quarta contribuição, exploramos a manufatura aditiva das resinas de alumínio- fosfato-silicato. Foi estudada a evolução dos parâmetros de impressão 3D desses materiais (energia crítica e profundidade de penetração) e da cinética de fotopolimerização com a intensidade de luz e a concentração de silicato. Os resultados obtidos indicaram um aumento da conversão critica das resinas com o aumento da concentração de silicato, o que estaria associado a uma maior contribuição da reação de ciclização. Esses resultados foram empregados para validar um modelo fotoquímico descrevendo a interação laser-resina em sistemas VPP publicados na literatura, elucidando a relação entre energia crítica e cinética de fotopolimerização. Em nossa última contribuição, estudamos a distribuição do índice de refração e a presença de anisotropias ópticas em linhas impressas 3D. Foi verificado que as peças impressas em 3D são opticamente homogêneas, apesar da presença de um gradiente de grau de polimerização associado à penetração do laser na resina e do perfil do feixe. Anisotropias ópticas foram identificadas, e medidas de espalhamento micro-Raman polarizado indicaram que a birrefringência e oriunda da tensão de cisalhamento perpendicular à direção da varredura causada pelo influxo de monômero em direção ao centro da polimerização.
Desenvolvimento de materiais híbridos aluminofosfato via rota sol-gel para manufatura aditiva de materiais fotônicos
Keywords: Three-dimensional printing; Photonics; Phosphates; Lanthanides; Optical properties